From bureaucracy to Artificial Intelligence: The tension between effectiveness and guarantees» Cedam Wolters Kluwer, Milán, 2023: Recensión a la obra de Eva Menéndez Sebastián - Navajas Rebollar, Miguel (Diálogos Jurídicos, 2024)
Sin resumen